2015
DOI: 10.1017/s1473550415000282
|View full text |Cite
|
Sign up to set email alerts
|

Origin of life: LUCA and extracellular membrane vesicles (EMVs)

Abstract: Cells from the three domains of life produce extracellular membrane vesicles (EMVs), suggesting that EMV production is an important aspect of cellular physiology. EMVs have been implicated in many aspects of cellular life in all domains, including stress response, toxicity against competing strains, pathogenicity, detoxification and resistance against viral attack. These EMVs represent an important mode of inter-cellular communication by serving as vehicles for transfer of DNA, RNA, proteins and lipids between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 121 publications
1
18
0
Order By: Relevance
“…A possible benefit of the production of OMVs in the environment and participation in the biomineralization of elements is an important environmental implication for mineral depositions. In a wider sense, extracellular vesicles or nanoglobules are intriguing objects in astrobiological discussions about origin of life and Lithopanspermia (McKay et al 1996 ;Kebukawa et al 2009 ;De Gregorio et al 2013 ;Gill and Forterre 2016 ).…”
Section: Biomobilization Of Inorganic Ions Bymentioning
confidence: 99%
“…A possible benefit of the production of OMVs in the environment and participation in the biomineralization of elements is an important environmental implication for mineral depositions. In a wider sense, extracellular vesicles or nanoglobules are intriguing objects in astrobiological discussions about origin of life and Lithopanspermia (McKay et al 1996 ;Kebukawa et al 2009 ;De Gregorio et al 2013 ;Gill and Forterre 2016 ).…”
Section: Biomobilization Of Inorganic Ions Bymentioning
confidence: 99%
“…A number of molecular and biochemical markers of viability of different forms of living organisms including microorganisms, spores and extracellular membrane vesicles (known as protocell nanoglobules), which potentially could serve as 'seeds' of life in the universe, have been proposed (Cohn, 1876;Arhenius, 1903;de Gregorio et al, 2013;Chen and Walde, 2010;Floss et al, 2014;Saha et al, 2014;Gill and Forterre, 2016). In the framework of the multipurpose international project "BIOlogical and Mars Experiment (BIOMEX)", a variety of organo-mineral samples were integrated into the EXPOSE-R2 platform to study vitality of pro-and eukaryotic organisms and stability of organic biomolecules as putative biomarkers (de Vera et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The progressive increase in complexity of bio-mineral complexes at cell emergence requires a critical step where a boundary occurs and separates the living cell system from its environment [ 44 , 45 , 46 ]. The compartmentalization of the primordial soup (i.e., the process that allowed the isolation and creation of a physico-chemical and thermodynamic environment suitable for the synthesis of bio-macromolecules) into vesicles would have favored the emergence of primitive life forms [ 47 ]. These authors also suggested that membrane vesicles could have a role in early cell evolution and may have helped shape the nature of LUCA, our Last Universal Common Ancestor.…”
Section: From Mineral To Biotic Entities: a Path Toward The Livingmentioning
confidence: 99%
“…These authors also suggested that membrane vesicles could have a role in early cell evolution and may have helped shape the nature of LUCA, our Last Universal Common Ancestor. Thus, lipid vesicles may have been the first protocells to concentrate RNA before the appearance of ribocells, ancestors of RNA-based cells, that preceded LUCA [ 47 ]. Beside this evolutionary theory, there is no doubt that extracellular vesicles (EVs) represent the smallest cell-like entities surrounded by a lipid structure.…”
Section: From Mineral To Biotic Entities: a Path Toward The Livingmentioning
confidence: 99%
See 1 more Smart Citation